Strategi Pengembangan Bisnis dalam Upaya Meningkatkan Penjualan Berbasis Media Sosial Terhadap Bisnis Kuliner di Pekanbaru - Reni Nasrianti; Susiwati (Kilau Publishing, 2026)
The main problem of this research is the suboptimal integrated use of social media by business actors to increase sales in culinary businesses in Pekanbaru City. The purpose of this research is to analyze social media-based business development strategies to increase sales. The research approach used a qualitative descriptive method. The research subjects consisted of four people: two business owners, one social media manager, and one consumer. Data collection techniques used observation, interviews, and documentation. Data analysis techniques used an interactive model that includes data reduction, data presentation, and drawing conclusions. The results show that social media is a primary marketing tool capable of increasing sales through content consistency, creativity, interaction with consumers, and the use of platforms such as Instagram, TikTok, and WhatsApp. The use of digital and analytical features is not optimal due to limited digital literacy of business actors. The research recommendations include improving digital literacy, data-based marketing training, and optimizing the use of social media features for more effective and sustainable marketing strategies.